أثر السنة وآثار السلف في حفظ الدين - لضفار, لمين (University of eloued جامعة الوادي, 2021)
"ملخص البحث يتناول هذا البحث قضيتين من قضايا الإسلام الكبرى وهي منزلة السنة ومكانتها من دين الإسلام، ومنزلة وفضل حملة السنة الأوائل من الصحابة رضي الله عنهم ومن اتصل بهم من أصحاب القرون الأولى؛ وقد زلت في القضيتين أقدام طوائف ممن انتسب إلى الإسلام، فوقع الجفاء تجاه النبي صلى الله عليه وسلم وسنته، ووقعت الفجوة والتنكر للسلف الصالح الذين ثبت فضلهم في نصوص الكتاب والسنة، واستهين بما كانوا عليه من علم واعتقاد وفهم وعمل؛ فجاء هذا البحث ليُظهر علو منزلة السنة بدلالة القرآن فضلا عن السنة، وأنه لا غنى لأحد بالقرآن عنها، ويُجلي الأدلة التي تقطع بخيرية أهل القرون الأولى، وسبقهم في كل خير، وأن الله عز وجل هيأهم لحمل ميراث النبوة وتبليغه، ولولا ثبوت عدالتهم -في الجملة- لما جعلهم الواسطة في نقل الوحي لمن بعدهم، وفيه بيان كيف بقي هذا الدين محفوظا-بحفظ الله- ثم بجهود أهل الحديث المجددين الذين اعتنوا بما ورثوه عن السلف من ميراث النبوة مقترنا بآثارهم في العلم والعمل التي كانت مثلا للوسطية التي ارتضاها الله عز وجل لعباده فكانوا فرقانا بين أهل الغلو والجفاء في كل عصر. "Thesis summary This thesis deals with two major subjects of Islam, which are the status of the Sunnah and its position in the religion of Islam, and the status and virtue of the early bearer of the Sunnah from the Companions, may God be pleased with them, and those who were in contact  with them from the first centuries; on these two subjects, sects of those who were affiliated to Islam slipped up, and estrangement occurred towards the Prophet ﷺ and his Sunnah, and a gap occurred with a denial of the pious predecessors whose virtues were proven in the texts of the Qur’an and Sunnah, and they underestimated their knowledge, belief, understanding and action. This thesis came to show the high status of the Sunnah in terms of the Qur’an as well as the Sunnah itself, and that no one can benefit from the Qur’an without it, and it clarifies the evidences about the benevolence of the people of the first centuries and their precedence in every best, and that God  prepared them to carry the inheritance of prophecy and communicate it, and if they were not proven to be fair - in general – he would not made them the intermediary in transmitting the revelation to those after them, and it explains how this religion remained preserved - by the protection of God - and then by the efforts of the Hadith scholars renovators who took care of what they inherited from the predecessors of the inheritance of prophecy coupled with their knowledge and work effects which were an example of the moderation that God accepted  for his servants, so they could differentiate  between the people of exaggeration and estrangement in every era. "
علوم حديث
Keywords: السنةالنبوية، السلف، حجية السنة النبوية، حفظ الدين.; The Sunnah, the Salaf, the authenticity of the Prophetic Sunnah, the preservation of the religion